A review of the indigenous coffee resources of Uganda and their potential for coffee sector sustainability and development - Davis, Aaron P.; Kiwuka, Catherine; Faruk, Aisyah; Mulumba, John; Kalema, James (Frontiers in Plant Science, 2023)
Uganda is a major global coffee exporter and home to key indigenous (wild) coffee resources. A comprehensive survey of Uganda’s wild coffee species was undertaken more than 80 years ago (in 1938) and thus a contemporary evaluation is required, which is provided here. We enumerate four indigenous coffee species for Uganda: Coffea canephora, C. eugenioides, C. liberica (var. dewevrei) and C. neoleroyi. Based on ground point data from various sources, survey of natural forests, and literature reviews we summarize taxonomy, geographical distribution, ecology, conservation, and basic climate characteristics, for each species. Using literature review and farm survey we also provide information on the prior and exiting uses of Uganda’s wild coffee resources for coffee production. Three of the indigenous species (not C. neoleroyi) represent useful genetic resources for coffee crop development (e.g. via breeding, or selection), including: adaptation to a changing climate, pest and disease resistance, improve agronomic performance, and market differentiation. Indigenous C. canephora has already been pivotal in the establishment and sustainability of the robusta coffee sector in Uganda, and has further potential for the development of this crop in Uganda. Coffea liberica var. dewevrei (excelsa coffee) is emerging as a commercially viable coffee crop plant in its own right, and may offer substantial potential for lowland coffee farmers, i.e. in robusta coffee growing areas. It may also provide useful stock material for the grafting of robusta and Arabica coffee, and possibly other species. Preliminary conservation assessments indicate that C. liberica var. dewevrei and C. neoleroyi are at risk of extinction at the country-level (Uganda). Adequate protection of Uganda’s humid forests, and thus its coffee natural capital, is identified as a conservation priority for Uganda.